Literatur Review: Efektivitas Pemberian Aromaterapi Peppermint Terhadap Pengurangan Mual dan Muntah pada Ibu Hamil Trimester I: Literature Review: The Effectiveness of Administering Peppermint Aromatherapy on Reducing Nausea and Vomiting in First Trimester Pregnant Women - Maria Oktavia; Ika Avrilina Haryono; Susanti Suhartati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: Nausea and vomiting of pregnancy or often referred to as